The foreign policies of Caribbean and Central American countries : selections from PROSPEL'S 1986 Las politicos exteriores de America Latina y el Caribe - Suchlicki, Jaime; Marchi, Jane G. (Miami, Florida : Institute of Inter-american Studies at the Graduate School of International Studies, University of Miami, 1990)
Continuedad en la crisis; edited by Heraldo Munoz
Keywords: Caribbean Area -- Foreign relations -- 1945-.; Central America -- Foreign relations -- 1979-.